Development of Smart E-Books ”caring strategies to prevent stunting during pregnancy" - Purwati, Yuni; Anisa, Diah Nur; Renitasari, Febriana (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background: Stunting is a health problem in Indonesia due to malnutrition during the first 1000 days of life (HPK), namely 270 days in the womb and 730 days after birth (until the age of two years), there are 30.8% of toddlers experiencing stunting. A caring strategy for preventing stunting is needed since pregnancy. Objective: The purpose of this study was to produce an electronic smart book as an educational media for preventing stunting since pregnancy. Methods: The method is a Research and Development modification of Borg & Gall: 1) Identification of needs; 2) designing smart e-books; 3) development; 4) expert validation; 5) revision. The validity of the material expert uses an 18-item checklist and a 7-item checklist of media expert validity. Results: the compilation of the smart e-book "Giring Nanting Hamil" (caring strategy for preventing stunting since pregnancy) which has been validated by 2 material experts with a result of 81% (very valid) and 2 media experts with a result of 80.33% (valid). Conclusion: a valid and feasible smart e-book "Giring Nanting Hamil" was produced. These results require follow-up trials on sample groups of pregnant women to determine the readiness and practices for preventing stunting since pregnancy.